Mobile applications and patient education: Are currently available GERD mobile apps sufficient?. (18th October 2016) - Bobian, Michael; Kandinov, Aron; El‐Kashlan, Nour; Svider, Peter F.; Folbe, Adam J.; Mayerhoff, Ross; Eloy, Jean Anderson; Raza, S. Naweed
Abstract : Objectives/Hypothesis: Despite the increasing role of mobile applications (apps) in patient education, there has been little inquiry evaluating the quality of these resources. Because poor health literacy has been associated with inferior health outcomes, evaluating the quality of patient education materials takes on great importance. Our objective was to employ validated readability tools for the evaluation of gastroesophageal reflux (GERD) mobile apps. Methods: GERD‐specific apps found in the Apple App Store (Apple Inc., Cupertino CA) were evaluated using the Readability Studio Professional Version 2015 for Windows (Oleander Software, Ltd, Vandalia, OH). All text was evaluated using nine validated algorithms measuring readability including Flesch‐Kincaid Grade Level, Simple Measure of Gobbledygook grading, Gunning Fog index, Coleman‐Liau, New Fog Count formula, Raygor Readability Estimate, FORCAST, Fry graph, and Flesch Reading Ease score. Results: Average reading grade levels for individual GERD apps ranged from 9.6 to 12.9 (interquartile range 10.3–12). The average reading grade level for all apps analyzed was 11.1 ± 0.2 standard error of the mean (SEM), with an average Flesch Reading Ease score for all mobile apps analyzed of 51 ± 2.05 (SEM), falling into the "fairly difficult" category given by this measure. Raygor Readability estimates that most mobile apps have a reading grade level between 10 and 12, with the majority of this outcome due to long words. Conclusion: This analysis demonstrates the feasibility of assessing readability of mobile health apps. Our findings suggest significant gaps in potential comprehension between the apps analyzed and the average reader, diminishing the utility of these resources. We hope our findings influence future mobile health‐related app development and thereby improve patient outcomes in GERD and other chronic diseases. Level of Evidence: NA. Laryngoscope, 127:1775–1779, 2017